2011
DOI: 10.1111/j.1600-0846.2011.00566.x
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional dielectric imaging for dermatologic screening: a feasibility study

Abstract: The electronic scanning probe used for the present study addresses existing limitations with current coaxial probes. Measurements of healthy and diseased areas of skin are provided to illustrate the feasibility of the approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Whilst these six individual studies were generally of a smaller malignant tissue sample size, all six studies were able to show that various bioimpedance parameters could be used to distinguish malignant from normal tissue. The studies of gastric adenocarcinoma, renal cell carcinomas, various thyroid malignancies and squamous cell skin cancer all showed malignant tissue to have lower impedance and/ or resistivity/permittivity than normal [55][56][57][58], whilst the colorectal and oesophageal studies showed higher impedance with malignant lesions compared to normal [58][59][60]. Additionally, the colorectal study showed that in two previously malignant lesions that had shown complete response to chemoradiotherapy, the impedance measurements appeared to be similar to that of normal colorectal tissue [58].…”
Section: Individual Studies Of Other Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst these six individual studies were generally of a smaller malignant tissue sample size, all six studies were able to show that various bioimpedance parameters could be used to distinguish malignant from normal tissue. The studies of gastric adenocarcinoma, renal cell carcinomas, various thyroid malignancies and squamous cell skin cancer all showed malignant tissue to have lower impedance and/ or resistivity/permittivity than normal [55][56][57][58], whilst the colorectal and oesophageal studies showed higher impedance with malignant lesions compared to normal [58][59][60]. Additionally, the colorectal study showed that in two previously malignant lesions that had shown complete response to chemoradiotherapy, the impedance measurements appeared to be similar to that of normal colorectal tissue [58].…”
Section: Individual Studies Of Other Cancersmentioning
confidence: 99%
“…Six other independent studies looked at the effects of the malignant process on the electrical conductivity of various tissue types, four of which were on in vivo specimens. The 6 individual tissue types included thyroid malignancies, squamous cell carcinomas of the skin, oesophageal adenocarcinoma and squamous cell carcinoma, gastric adenocarcinoma, colorectal adenocarcinoma and renal cell carcinoma [55][56][57][58][59][60]. Whilst these six individual studies were generally of a smaller malignant tissue sample size, all six studies were able to show that various bioimpedance parameters could be used to distinguish malignant from normal tissue.…”
Section: Individual Studies Of Other Cancersmentioning
confidence: 99%